The Application of the Probatory Immaculation Principle in the Exercise of the Supervisory Function of Regulatory Agencies - León Pacheco, José Francisco (2015)
This article starts by analyzing the concept of Due Process and its scope over the administrative procedures. Also, the concept of the Right to Evidence, as an element of Due Process, is explained. Then, an analysis of the relationship between the supervisory procedures and the Due Process is developed, in order to check whether if its requirements are fulfilled by the Public Administration in order to obtain a Valid Evidence after a monitoring or an inspection. Finally, the analysis is focused on the actions of the Peruvian Regulatory Agencies, specifically, during the issuing of an Inspection Report after a Supervisory Procedure.